Disorder-induced metal-insulator transition in cooled silver and copper nanoparticles: A statistical study - Sandonas, LM (2017)
The existence of a disorder-induced metal-insulator transition (MIT) has been proved in cooled silver and copper nanoparticles by using level spacing statistics. Nanoparticles are obtained by employing molecular dynamics simulations. Results show that structural disorder is not strong enough to affect their electronic character, and it remains in the metallic regime. Whereas, electronic properties cross to the insulating regime after increasing the chemical disorder strength.